AN OBSERVATIONAL TEST OF THE ORIGIN OF ACCELERATING MOMENT RELEASE BEFORE LARGE EARTHQUAKES - Mignan A.; King G.C.P.; Bowman D.D. (My University, 2006)
A progressive increase of seismic activity distributed over a wide region around a future earthquake epicenter is termed accelerating moment release (AMR). This phenomenon has been observed in several studies over the last 15 years, although there is no consensus about the physical origin of the effect. In a recent hypothesis known as the stress accumulation (SA) model, the AMR is thought to result from the last stage of loading in the earthquake cycle. In this view, the increasing seismicity is due to minor stress release as the whole region becomes sufficiently stressed for the major event to occur. The stress accumulation model makes specific predictions about the distribution of events in an AMR sequence. Because the AMR is predicted to be a result of loading on the main fault, the precursory activity should be concentrated in the positive lobes of the far-field stresses calculated by a backslip dislocation model of the main shock. To test this model, AMR is first found in optimal circular regions around the epicenters of each of the Mw ≥ 6.5 earthquakes in central and southern California since 1950. A backslip dislocation model is then used to determine which of the precursory events occur in the regions predicted by stress accumulation. AMR is shown to occur preferentially in the lobes of the backslip stress field predicted by the stress accumulation model. Copyright 2006 by the American Geophysical Union.